Comprehensive remediation study of disperse dyes in wastewater using cenospheres nanosyntactic foam. (1st May 2018) - Markandeya,; Dhiman, Nitesh; Shukla, Sheo P.; Mohan, Devendra; Kisku, Ganesh C.; Patnaik, Satyakam
Abstract: The aim of present study is to clean the dye contaminated wastewater in an efficient and environmentally affordable manner using coal fly ash, a waste by-product of thermal power plant. Initially, the low densities, inert and hollow cenospheres were segregated from coal fly ash which are blended with chitosan in 3:10 stoichiometric ratio via glutaraldehyde cross-linking to prepare chitosan-cenospheres nanosyntactic foam. Further, batch adsorption studies were performed to achieve amplified removal of Disperse Orange 25 and Disperse Blue 79:1 dyes from wastewater with respect to various operational parameters such as pH, adsorbent dose, dye concentration, agitation speed, contact time and temperature. Maximum removal of 90% in case of Disperse Orange 25 and 87% in case of Disperse Blue 79:1 dye were obtained at an optimized nanosyntactic foam dose of 0.2 g/L at pH 6 with agitation speed of 200 rpm at 40 mg/L dye concentrations. Interestingly, the high adsorption capacity of chitosan-cenospheres nanosyntactic foam (∼500.0 mg/g) at 45 °C establishes the superiority of the aforementioned technique compared to works reported earlier for dyes removal. Furthermore, isotherm and kinetic studies along with thermodynamic parameters substantiated that spontaneous and exothermic monolayer adsorption of the dyes occur onto chitosan-cenospheres nanosyntactic foam following pseudo second order reaction kinetics. Reusability of chitosan-cenospheres nanosyntactic foam for four successive runs were carried out to ensure sustainable use of this adsorptive technique. The present work offers a pragmatic tool for water pollution abatement control, especially pollution from textile effluents by utilizing a waste by-product as adsorbent. Graphical abstract: Schematic illustration of the synthesis and adsorption behavior of the Cs -Cn nanosyntactic foam.Image Highlights: A biosorbent Chitosan-Cenospheres (Cs-Cn) nanosyntactic foam for Dye removal. ATR-FTIR, SEM, TEM, EDX, XRD, DLS and BET techniques used to confirm the synthesis. Batch experiments and statistical analysis were performed for optimized result. Isotherm, kinetics, intra-particle diffusion and thermodynamics were also analyzed. Cs-Cn nanosyntactic foam reusability was assessed up to 4 successive cycles.